Diffusiophoretic exclusion of colloidal particles for continuous water purification. Issue 12 (24th May 2018) - Lee, Hyomin; Kim, Junsuk; Yang, Jina; Seo, Sang Woo; Kim, Sung Jae
Abstract : A micro/nanofluidic device for continuous water purification utilizing long-range diffusiophoretic migration around ion exchangeable surfaces. Abstract : It has been observed that colloidal particles are anomalously repelled from the interface of nanoporous materials and water by up to hundreds of micrometers even if there is no additional external field present. Recently, the physical origin of this anomalous repulsion has turned out to be diffusiophoretic migration triggered by an ion exchange process through the interface. Since the repulsive force is induced by a salt gradient only, the phenomenon can be applied to a microscale water purification platform without the need for any external power sources. In this work, we suggest a micro/nanofluidic device for continuous water purification utilizing long-range diffusiophoretic migration around ion exchangeable surfaces. An ion concentration boundary layer was characterized by the Sherwood number (Sh) which is a key dimensionless number to describe the purification process. Depending on Sh, we have theoretically and experimentally demonstrated that long-range diffusiophoretic exclusion can be used for continuous water purification. Finally, our platform can be used as a highly energy-efficient and portable water treatment option for operations such as purification, disinfection, water softening, etc.